The Effect of Self-Efficacy on Gpa of Undergraduate Program Students in Maluku - Criezta Korlefura; Theophanny Rampisela (Peneliti.net, 2022)
Self-efficacy can help a person to master the situation and create positive results. Self-efficacy has a strong influence on behavior. This study aims to see that the effect of self-efficacy on student achievement is seen from the student's GPA. Students who have high self-efficacy will have high learning achievement and vice versa. The research method used in this study is a quantitative research method. The population in this study were students of the Guidance and Counseling Study Program, FKIP University of Pattimura, batch 2021. The self-efficacy measuring instrument is divided into three domains, namely, magnitude level, generality, and strength. The majority of respondents in this study were female, as many as 40 people out of 44 respondents. The age range of the respondents in this study was 18 to 25 years. Based on the results of hypothesis testing, it is found that the relationship between self-efficacy and GPA is by using the correlation number between the two variables, the correlation number is .313 with a significance level of .000. This means that there is a significant relationship between self-efficacy and GPA.